Analisis Resepsi Mahasiswa UMY, UTY, dan UGM terhadap Penggunaan Idol Korea dalam Iklan Produk Scarlet whitening - Vicky Rosanda Putri Avi; Fajar Junaedi (Universitas Muhammadiyah Klaten, 2026)
Abstract This study aims to analyze the reception of students from Muhammadiyah University of Yogyakarta (UMY), Yogyakarta University of Technology (UTY), and Gadjah Mada University (UGM) toward the use of Korean idols as brand ambassadors in advertisements for the local beauty product Scarlett Whitening. The research uses a qualitative approach with Stuart Hall's reception analysis method thru structured interviews with five students who have knowledge of Scarlett Whitening advertisements and Korean Wave (Hallyu) culture. The research findings indicate that audience reception is divided into three positions of meaning: dominant-hegemonic, negotiated, and oppositional. The majority of informants were in dominant-hegemonic and negotiating positions, indicating acceptance of the global appeal of Korean idols in strengthening product image and trust, but still accompanied by critical awareness of the differences between Korean beauty standards and the local cultural context of Indonesia. Meanwhile, the opposition's position represents a rejection of foreign cultural dominance, which is seen as potentially eroding local identity. This finding confirms that the student audience plays an active role in interpreting advertising messages, and also shows that Scarlett Whitening's advertisements not only serve as a promotional medium but also as a space for cultural negotiation between global and local values in the flow of globalization. Keywords: brand ambassador, Korean idol, Scarlett Whitening, beauty advertisement, Korean Wave (Hallyu)